Magnetic Relaxometry with an Atomic Magnetometer and SQUID Sensors on Targeted Cancer Cells - Johnson, Cort (2012)
Magnetic relaxometry methods have been shown to be very sensitive in detecting cancer cells and other targeted diseases. Superconducting Quantum Interference Device (SQUID) sensors are one of the primary sensor systems used in this methodology because of their high sensitivity with demonstrated capabilities of detecting fewer than 100,000 magnetically-labeled cancer cells. The emerging technology of atomic magnetometers (AM) represents a new detection method for magnetic relaxometry with high sensitivity and without the requirement for cryogens. We report here on a study of magnetic relaxometry using both AM and SQUID sensors to detect cancer cells that are coated with superparamagnetic nanoparticles through antibody targeting. The AM studies conform closely to SQUID sensor results in the measurement of the magnetic decay characteristics following a magnetization pulse. The AM and SQUID sensor data are well described theoretically for superparamagnetic particles bound to cells and the results can be used to determine the number of cells in a cell culture or tumor. The observed fields and magnetic moments of cancer cells are linear with the number of cells over a very large range. The AM sensor demonstrates very high sensitivity for detecting magnetically labeled cells does not require cryogenic cooling and is relatively inexpensive.